Comparison of molecular techniques for the detection of Toxoplasma gondii in raw bovine milk from small rural properties in Brazil - Manzini, Suzane [UNESP]; Bertozzo, Thainá Valente [UNESP]; Aires, Isabella Neves [UNESP]; Rodrigues, Nássarah Jabur Lot [UNESP]; Bertolini, Amanda Bezerra [UNESP]; Alexandrino, Marcela [UNESP]; Steinle, Jackieline Sampaio [UNESP]; de Melo, Renata Pimentel Bandeira; Mota, Rinaldo Aparecido; de Medeiros, Maria Izabel Merino; Richini-Pereira, Virgínia Bodelão; Curci, Vera Cláudia Lorenzetti Magalhães; et al. (Elsevier, 2024)
This study aimed to research Toxoplasma gondii DNA in 102 samples of raw bovine milk from expansion tanks, in small properties located in different cities of the Midwest region of São Paulo, Brazil. For this, polymerase chain reaction (PCR) was performed with the primers TOX4/TOX5 for cPCR (conventional PCR), TgNP1/TgNP2 gene for nested PCR and the Tg18s58F/Tg18s348R for nested PCR. It was possible to detect T. gondii DNA in 18 (17.65 %) milk samples from the 102 tanks, corresponding to 4.90 % for TOX4/TOX5 primers, 12.74 % for TgNP1/TgNP2 gene and 0.98 % for Tg18s58F/Tg18s348R gene. The results showed that the TgNP1 and TgNP2 genes were more efficient to detect T. gondii DNA, and also indicated the importance of raw bovine milk as a source of human infections caused by this protozoan, being a public health problem. It is important to continue studies involving T. gondii from bovine milk considering the need for proper pasteurization, and for better comprehension regarding the epidemiology of this protozoan.
Keywords: Bulk tank milk; Detection; Milk; Toxoplasmosis; Zoonosis